Hyperopia in young people: risk factors and prognosis at the CADES/O of the Donka National Hospital Guinea - Balde, Abdoul Karim; A, Tchevede J; MD, Sovogui; TM, Bah; A, Magassouba; K, Barry A; S, Diané (Jour Med Resh and Health Sci, 2022)
SUMMARY Objective: To study hyperopia in young people aged 1 to 40 years at the CADES/O of the Donka NationalHospital. Method: This is a prospective descriptive study of young subjects aged between 1 and 40 years who were seen in an ophthalmology consultation during the period from 1er October 2020 to 31 January 2021, and who werediagnosed with hyperopia after an automatic refractometry under cycloplegia. Results: Hyperopia with risk factors had a frequency of 89.9% among the young hyperopic subjects. Of the 170young hyperopic subjects with risk factors, the majority were between 11 and 20 years of age (51.8%). Females were predominant (68.2%). The majority of the young hyperopic subjects had a secondary or university education(36.5%); and the most represented occupation was that of pupils or students (76.5%). Outdoor activities (78.8%)and the wearing of glasses by at least one parent before the age of 40 (48.2%) were the main risk factors found.Low hyperopia was the most frequently observed degree of hyperopia (84.1% OD and 75.4% OG). Only 3.2% ofyoung hyperopic subjects had a complication. Conclusion: Hyperopia is mostly found in young people between 11 and 20 years of age and is often of low degree. Several risk factors such as genetic factors, and prolonged practice of outdoor activities, favour theoccurrence of hyperopia.